Multi-color single-molecule tracking and subtrajectory analysis for quantification of spatiotemporal dynamics and kinetics upon T cell activation - Yuma Ito (Nature Portfolio, 2017)
Abstract The dynamic properties of molecules in living cells are attracting increasing interest. We propose a new method, moving subtrajectory analysis using single-molecule tracking, and demonstrate its utility in the spatiotemporal quantification of not only dynamics but also the kinetics of interactions using single-color images. Combining this technique with three-color simultaneous single-molecule imaging, we quantified the dynamics and kinetics of molecules in spatial relation to T cell receptor (TCR) microclusters, which trigger TCR signaling. CD3ε, a component of the TCR/CD3 complex, and CD45, a phosphatase positively and negatively regulating signaling, were each found in two mobility states: faster (associated) and slower (dissociated) states. Dynamics analysis suggests that the microclusters are loosely composed of heterogeneous nanoregions, possibly surrounded by a weak barrier. Kinetics analysis quantified the association and dissociation rates of interactions with the microclusters. The associations of both CD3ε and CD45 were single-step processes. In contrast, their dissociations were each composed of two components, indicating transient and stable associated states. Inside the microclusters, the association was accelerated, and the stable association was increased. Only CD45 showed acceleration of association at the microcluster boundary, suggesting specific affinity on the boundary. Thus, this method is an innovative and versatile tool for spatiotemporal quantification.